2001
DOI: 10.4282/sosj.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory culture of Balanus trigonus larvae by the method of B. amphitrite for establishing a multi-species settlement assay.

Abstract: In the study of antifouling, it is important to establish a method for culturing barnacle larvae for settlement assays. In the laboratory, the diatom Chaetoceros gracilis has been shown to be one of the best diets for raising the larvae of Balanus amphitrite. We applied this culture method to B. trigonus, supplying of rate of development to the cyprid stage, and the survival rates at different food concentrations, indicated survival rate on the sixth day following the start of culture was 84%, and about 71% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These kinds of techniques have been successful for other barnacles so far. Laboratory cultures of Balanus amphitrite larvae (Qiu and Qian, 1997), Balanus trigonus larvae (Mishra, et al, 2001), Megabalanus rosa larvae (Kado and Hirano, 1994;Okano et al, 1996;Yoshimura et al, 2006), Megabalanus volcano (Kado and Hirano, 1994) and Chinochthamalus scutelliformis larvae (Yan, 2003) have also been reported. By contrast, little has been reported on laboratory cultures of B. rostratus.…”
Section: Discussionmentioning
confidence: 96%
“…These kinds of techniques have been successful for other barnacles so far. Laboratory cultures of Balanus amphitrite larvae (Qiu and Qian, 1997), Balanus trigonus larvae (Mishra, et al, 2001), Megabalanus rosa larvae (Kado and Hirano, 1994;Okano et al, 1996;Yoshimura et al, 2006), Megabalanus volcano (Kado and Hirano, 1994) and Chinochthamalus scutelliformis larvae (Yan, 2003) have also been reported. By contrast, little has been reported on laboratory cultures of B. rostratus.…”
Section: Discussionmentioning
confidence: 96%
“…Immediately after cyprid larval settlement, they undergo metamorphosis, adopting the form of an adult specimen, where factors such as depredation, competition and physical disturbances (Gaines & Roughgarden, 1985;Minchinton andScheibling, 1991, Thomason et al, 1998) play an important role in the early survival of individuals. Under laboratory conditions, it has been described how aspects, such as type and concentration of food, temperature and larval density are key factors influencing duration and survival during larval development (Qiu and Qian, 1999;Mishra et al, 2001;Thiyagarajan et al, 2003a;2003b). In addition, with respect to induction of larval settlement, it has been observed that a great variety of chemical signals trigger this response, associated, principally, with three types of source: presence of conspecific indivuduals, presence of prey species and microbial films (Rodríguez et al, 1992).…”
Section: Biological Characteristicsmentioning
confidence: 99%
“…Microalgae densities of the genera Chaetoceros sp, Skeletonema and Isochrysis, vary from 1x10 5 to 10x10 5 cells/ml. In this species, survival has exceeded 90% (Qiu and Quian, 1999;Mishra et al, 2001). Percentage of larval settlement can vary from 10% to 80%, depending on the culture conditions, the substrate type and the use of inductors (Rittschoff et al, 1984;Mishra and Kitamura, 2000;Mishra et al, 2001;Thiyagarajan et al, 2003b).…”
Section: )mentioning
confidence: 99%
“…Barnacle larvae production efforts in the laboratory date back to over 50 years ago (Knight‐Jones 1953; Costlow & Bookhout 1958), and different records of methodologies and larvae culture conditions are available (Brown & Roughgarden 1985; Qiu & Qian 1999; Mishra, Kitamura & Tomoda 2001; Thiyagarajan, Harder & Qian 2003). Similarly, energetic and behavioural aspects of the cypris have been studied (Keough & Downes 1982; Khandeparker, Anil & Raghukumar 2002; Thiyagarajan, Harder, Qiu & Qian 2003), in addition to inductor and inhibitor effects on larval settlement and metamorphosis (Gabbott & Larman 1987; Maki, Rittschof, Costlow & Mitchell 1988; Matsumura, Hills, Thomason, Thomason & Clare 2000; Dreanno, Kirby & Clare 2007; Tremblay, Bourget & Rittschof 2007; Qiu, Hung & Qian 2008).…”
Section: Barnacle Aquaculturementioning
confidence: 99%